Homogeneity Test of Response Rate Functions in Bilateral Correlated Data under Dallal’s Model - Hengyi Zhao; Xiaojuan Wang; Jingwen Bian; Shenglong Chen; Zhiming Li (Complexity)
In clinical studies, paired binary metadata are often encountered during collecting information from paired organs or parts. The risk difference, relative risk ratio, and odds ratios of response rates are widely used to measure cured effects for such data. Under Dallal’s model, the paper extends these measures to the general case in g groups. We propose eight test statistics for various functions when the dependency measures γii=1,…,g are equal or not. Simulation results show that the Score and Rosner-type tests can produce robust empirical type I error rates, while Wald-type and likelihood ratio tests have better power in testing the risk difference, relative risk ratio, and odds ratios. Finally, two real examples illustrate our proposed method’s practicability.